2004
DOI: 10.1152/ajpendo.00473.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of acidosis-induced increases in calcium on PTH secretion in acute metabolic and respiratory acidosis in the dog

Abstract: of acidosis-induced increases in calcium on PTH secretion in acute metabolic and respiratory acidosis in the dog. Am J Physiol Endocrinol Metab 286: E780 -E785, 2004. First published January 13, 2004 10.1152/ajpendo.00473.2003.-Recently, we showed that both acute metabolic acidosis and respiratory acidosis stimulate parathyroid hormone (PTH) secretion in the dog. To evaluate the specific effect of acidosis, ionized calcium (iCa) was clamped at a normal value. Because iCa values normally increase during acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 25 publications
(37 reference statements)
4
26
2
1
Order By: Relevance
“…The present findings of increases in the total plasma calcium, free ionized calcium, and free ionized magnesium after 21-day chronic metabolic acidosis were consistent with previous reports in rats and dogs (8,35). López and colleagues (35) have demonstrated that metabolic acidosis increased free ionized calcium within 10 min after in vivo acidotic induction.…”
Section: Discussionsupporting
confidence: 93%
“…The present findings of increases in the total plasma calcium, free ionized calcium, and free ionized magnesium after 21-day chronic metabolic acidosis were consistent with previous reports in rats and dogs (8,35). López and colleagues (35) have demonstrated that metabolic acidosis increased free ionized calcium within 10 min after in vivo acidotic induction.…”
Section: Discussionsupporting
confidence: 93%
“…Acidosis induces an increase in PTH secretion (27), probably as a result of a decreased calcium sensing of the parathyroid cells (28). Animal data indicate that the acidosis-induced increase of iCa attenuates but does not eliminate the increase of PTH secretion (29). Consistent with these data, we observed an association between high PTH and low bicarbonate, independent from iCa (data not shown).…”
Section: Discussionsupporting
confidence: 87%
“…These in vitro data are consistent with observations that metabolic acidosis is associated with increased serum PTH and calcium levels and that alkalosis suppresses serum PTH in vivo. 4,[6][7][8] The current findings suggest a CaR-based mechanism for these previous data from animal studies. It will be interesting therefore to determine therefore whether acidosis and/or alkalosis elicit chronic changes in PTH secretion in vivo.…”
Section: +supporting
confidence: 67%
“…In animal experiments, induction of metabolic acidosis results in increased serum PTH levels and hypercalcemia, whereas induction of alkalosis suppresses serum PTH levels. [4][5][6][7][8] Therefore, because acidosis has been associated with increased serum PTH levels in vivo, we examined whether much smaller, pathophysiologically relevant changes in pH o (60.2) can alter the Ca 2+ o sensitivity of CaR-mediated signaling pathways in HEK-293 cells and whether such effects can be replicated in parathyroid cells. We also examined whether a specific histidine or free cysteine residue could account for CaR pH o sensitivity and, finally, considered the effect of such pathophysiologic changes in pH o on PTH secretion.…”
Section: +mentioning
confidence: 99%